2009
DOI: 10.1152/japplphysiol.91277.2008
|View full text |Cite
|
Sign up to set email alerts
|

Long-loop pathways in cardiovascular electroacupuncture responses

Abstract: Li P, Tjen-A-Looi SC, Guo Z, Fu L, Longhurst JC. Long-loop pathways in cardiovascular electroacupuncture responses. J Appl Physiol 106: 620 -630, 2009. First published December 12, 2008 doi:10.1152/japplphysiol.91277.2008.-We have shown that electroacupuncture (EA) at P 5-6 (overlying median nerves) activates arcuate (ARC) neurons, which excite the ventrolateral periaqueductal gray (vlPAG) and inhibit cardiovascular sympathoexcitatory neurons in the rostral ventrolateral medulla (rVLM). To investigate whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
151
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(161 citation statements)
references
References 27 publications
10
151
0
Order By: Relevance
“…Previous neuronal electrophysiological and pharmacological studies from our group (29,30,50) suggest that EA increases vlPAG glutamate, since EA at P5-6 increases splanchnic nerve stimulation of vlPAG neuronal activity and because microinjection of DLH into the vlPAG decreases blood pressure and the rVLM neuronal activity. However, in the present study we did not observe an increase in glutamate in the vlPAG during EA.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Previous neuronal electrophysiological and pharmacological studies from our group (29,30,50) suggest that EA increases vlPAG glutamate, since EA at P5-6 increases splanchnic nerve stimulation of vlPAG neuronal activity and because microinjection of DLH into the vlPAG decreases blood pressure and the rVLM neuronal activity. However, in the present study we did not observe an increase in glutamate in the vlPAG during EA.…”
Section: Discussionmentioning
confidence: 75%
“…Electroacupuncture modulates vlPAG release of GABA through presynaptic cannabinoid CB1 receptors. J Appl Physiol 106: 1800 -1809, 2009. First published April 9, 2009 doi:10.1152/japplphysiol.91648.2008.-Previous studies have demonstrated that electroacupuncture (EA) attenuates sympathoexcitatory reflex responses by activating a long-loop pathway involving the hypothalamic arcuate nucleus (ARC), midbrain ventrolateral periaqueductal gray (vlPAG), and rostral ventrolateral medulla (rVLM).…”
mentioning
confidence: 99%
“…The mechanism of this excitation is not clear at this time and may involve pre-and/or postsynaptic effects of ANG-(1-12). Direct projections from the ARCN to the PVN, raphe nuclei, rostral ventrolateral medullary pressor area, and intermediolateral cell column of the thoracolumbar cord may mediate the increases in MAP, HR, and GSNA elicited by microinjections of ANG- (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12) into the ARCN (6,9,25,43). We (31) have previously shown that pressor responses elicited by microinjections of NMDA into the ARCN are mediated via the activation of ionotropic glutamate receptors (iGLURs) in the spinal cord.…”
Section: Discussionmentioning
confidence: 97%
“…Surgical and experimental protocols were approved by the Animal Use and Care Committee at the University of California, Irvine. Adult male Sprague-Dawley rats (350 -500 g) were used for microinjection of a retrogradely transported microsphere tracer in the nucleus ambiguus to evaluate direct projections from the NTS to the nucleus ambiguus, as described in detail in our previous studies (23). Ketamine-xylazine (80/12 mg/ml, Sigma, St. Louis, MO) was used to induce (0.3-0.4 ml im) and maintain (0.1-0.2 ml im) anesthesia in the animals.…”
Section: Anatomical Studiesmentioning
confidence: 99%
“…Modulation of cardiovascular function and elevated sympathetic activity is effective with low frequency and voltage stimulation of electroacupuncture (EA) at specific acupoints P5-6 positioned to activate the underlying median nerves (44 -46). Bilateral stimulation of P5-6 acupoints activates thinly myelinated and unmyelinated sensory fibers in the median nerve and neural pathways that project to cardiovascular-related regions in the central nervous system, which regulate autonomic activity and hence hemodynamic responses (21,23,39). Nuclei in the hypothalamus, midbrain, and medulla process this somatic input during EA to modulate sympathoexcitatory reflex responses (26,28,43).…”
mentioning
confidence: 99%